Making Complex Technologies Accessible Through Simple Controllability: Initial Results of a Feasibility Study - Pascal Müller; Hari Krishna Reddy Gali; Subashkumar Rajanayagam; Stefan Twieg; Patrick Jahn; Sebastian Hofstetter (Applied Sciences)
Digital assistive technologies (DATs) present a significant opportunity to address the challenges of the healthcare system. However, they have not been designed for this purpose and are still in the process of further development. The objective of this study is to ascertain the extent to which a digital cross-device control and application platform for the simplified utilization of DATs alters the willingness of nurses to utilize them in the care process. An exploratory, longitudinal design with a mixed-methods approach was employed in this study. The co-creative design cycle was conducted in two long-term care facilities, with 25 caregivers participating in the form of testing for the platform’s prototypes across multiple iteration loops. The preliminary results indicate a high intention to use DAT, suggesting that the actual use of DAT through a control and application platform will be considerable. The overall trend demonstrates an increase in acceptance, willingness, and intention to use DAT among the participants. One proposed solution to the usability issues of DAT is to develop a platform with an interface for non-programmers to create individual interventions using everyday controls and a few intuitive steps. This could facilitate the sustainable implementation of DAT in healthcare.